Sealing film, electrode lead wire member and battery
The sealing film with anhydrous layers and fluororesin intermediate layer addresses moisture intrusion in secondary batteries and capacitors, ensuring easy sealing and improved moisture resistance.
Patent Information
- Application Number
- JP2020037625
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-03-05
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2040-03-05
AI Technical Summary
Existing secondary batteries and capacitors face issues with moisture intrusion, which leads to water and electrolyte reaction and deterioration, necessitating improved sealing technologies.
A sealing film with an electrode adhesive layer, a sealant layer, and an intermediate layer, where the electrode adhesive and sealant layers are anhydrous, and the intermediate layer is made of fluororesin, with specific thickness ratios, effectively suppressing moisture intrusion.
The sealing film provides easy sealing and effective moisture barrier properties, enhancing the reliability and durability of batteries and capacitors by preventing moisture ingress.
Smart Images

Figure 0007613838000005 
Figure 0007613838000006 
Figure 0007613838000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a sealing film, an electrode lead member, and a battery. [Background technology]
[0002] In recent years, secondary batteries such as lithium-ion batteries and capacitors have been attracting attention as storage batteries for storing electrical energy.
[0003] For example, these secondary batteries and capacitors use storage containers made of a laminate for battery exteriors, which has excellent waterproofing and light-shielding properties. The laminate for battery exteriors is, for example, a laminate in which a base layer made of polyamide or polyester and aluminum foil are laminated. The electrode lead wires of the secondary batteries and capacitors connect the inside and outside of the storage container, and one end of the electrode lead wire protrudes from the storage container to the outside and is sealed.
[0004] A known configuration of such secondary batteries or capacitors is to interpose a sealing film, which is a resin laminate, between the container and the electrode lead wire. The sealing film prevents the formation of gaps around the electrode lead wire, thereby preventing moisture from entering the secondary battery or capacitor from around the electrode lead wire. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-7268 A Summary of the Invention [Problem to be solved by the invention]
[0006] It is known that when moisture penetrates into the container of a secondary battery or capacitor, the water reacts with the electrolyte and deteriorates the battery. To improve the reliability of secondary batteries and capacitors, a technology that is more effective than the current technology for preventing moisture penetration is needed.
[0007] The present invention has been made in view of the above circumstances, and has an object to provide a sealing film that is easy to seal and to easily suppress the intrusion of moisture. Another object of the present invention is to provide an electrode lead member having such a sealing film. Another object of the present invention is to provide a battery having such an electrode lead member. [Means for solving the problem]
[0008] In order to solve the above problems, one aspect of the present invention includes the following aspects.
[0009] [1] A sealing film having an electrode adhesive layer, a sealant layer, and an intermediate layer provided between the electrode adhesive layer and the sealant layer, wherein the electrode adhesive layer and the sealant layer contain maleic anhydride modified polyolefin, the intermediate layer contains a fluororesin, and a thickness of the intermediate layer is 30% or more and 75% or less of a total thickness of the sealing film.
[0010] [2] The sealing film according to [1], wherein the thickness of the intermediate layer is equal to or greater than the thickness of the electrode adhesive layer.
[0011] [3] The sealing film according to [1] or [2], wherein the thickness of the intermediate layer is equal to or greater than the thickness of the sealant layer.
[0012] [4] The sealing film according to any one of [1] to [3], wherein the fluororesin is polychlorotrifluoroethylene.
[0013] [5] The sealing film according to any one of [1] to [4], wherein the sealant layer contains at least one of maleic anhydride modified polyethylene and maleic anhydride modified polypropylene.
[0014] [6] An electrode lead member having an electrode lead extending in one direction and the sealing film described in any one of [1] to [5].
[0015] [7] An electrode lead wire member as described in [6], which has a pair of sealing films that sandwich the electrode lead wire, and the pair of sealing films are in contact with each other with the electrode adhesive layers facing each other and in contact with the entire circumferential circumference of the electrode lead wire to cover the electrode lead wire.
[0016] [8] The electrode lead wire member described in [6] or [7], wherein the electrode lead wire has a lead wire body and a surface treatment layer formed on the surface of the lead wire body, and the sealing film is provided in contact with the surface treatment layer at the electrode adhesive layer.
[0017] [9] A battery comprising the electrode lead member according to any one of [6] to [8]. Effect of the Invention
[0018] According to the present invention, it is possible to provide a sealing film that is easy to seal and to easily suppress the intrusion of moisture. It is also possible to provide an electrode lead member having such a sealing film. It is also possible to provide a battery having such an electrode lead member. [Brief description of the drawings]
[0019] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a sealing film 1 of an embodiment. [Diagram 2] FIG. 2 is a schematic perspective view showing an electrode lead member of the embodiment. [Diagram 3] FIG. 3 is a schematic perspective view showing the battery 100 of the embodiment. [Figure 4] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. [Diagram 5] FIG. 5 is an explanatory diagram showing a method for producing the test piece used in the examples. [Figure 6] FIG. 6 is an explanatory diagram showing a method for producing a test piece used in the examples. [Figure 7] FIG. 7 is a cross-sectional view of a test piece used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The sealing film, electrode lead wire member, and battery according to the present embodiment will be described below with reference to Figures 1 to 4. In all the following figures, the dimensions and ratios of the components are appropriately changed to make the drawings easier to see.
[0021] <Sealing film, electrode lead wire material> Fig. 1 is a schematic cross-sectional view showing a sealing film 1 of the present embodiment. Fig. 2 is a schematic perspective view showing an electrode lead member of the present embodiment.
[0022] The sealing film 1 has an electrode adhesive layer 2 , a sealant layer 3 , and an intermediate layer 4 . The electrode lead member 10 includes an electrode lead 11 and a sealing film 1. The following explains each in order.
[0023] (electrode adhesive layer) The electrode adhesive layer 2 is a layer that is fused to the electrode lead wire 11 by application of heat and pressure. The surface of the electrode adhesive layer 2 is one surface 1a of the sealing film 1.
[0024] The electrode adhesive layer 2 mainly contains an acid-modified polyolefin. In this specification, the electrode adhesive layer 2 "mainly contains an acid-modified polyolefin" means that the content of acid-modified polyolefin is the highest among the resins constituting the electrode adhesive layer 2. The electrode adhesive layer 2 preferably contains 50% by mass or more of acid-modified polyolefin based on the total amount of the electrode adhesive layer 2. The electrode adhesive layer 2 preferably contains 80% by mass or more of acid-modified polyolefin based on the total amount of the electrode adhesive layer 2.
[0025] In the electrode adhesive layer 2, optional components other than the acid-modified polyolefin include known additives such as stabilizers, antistatic agents, and colorants.
[0026] As the acid-modified polyolefin, acid-modified polypropylene is preferable because of its excellent heat resistance. Hereinafter, polypropylene may be abbreviated as "PP."
[0027] The acid-modified PP is a polymer obtained by graft-copolymerizing a monomer having a carboxy group onto polypropylene or an ethylene-propylene copolymer. The ethylene-propylene copolymer is preferably a random copolymer or a block copolymer.
[0028] Examples of the monomer having a carboxy group include unsaturated carboxylic acids such as acrylic acid and methacrylic acid, unsaturated carboxylic acid esters such as ethyl acrylate, and acid anhydrides such as maleic anhydride.
[0029] Acid-modified PP includes ionomers in which the carboxylic acid groups of an acid-modified polymer of polypropylene or an acid-modified polymer of ethylene-propylene copolymer are neutralized with a metal hydroxide, an alkoxide, a salt of a lower fatty acid, or the like.
[0030] The acid group of the acid-modified PP is preferably a maleic anhydride group, that is, the acid-modified PP is preferably maleic anhydride-modified PP.
[0031] The melting point of the resin constituting the electrode adhesive layer 2 is preferably 100° C. or higher and 160° C. or lower. When the “resin constituting the electrode adhesive layer 2” is a polymer alloy of two or more types of resin, the “melting point of the resin constituting the electrode adhesive layer 2” means the melting point of the polymer alloy constituting the electrode adhesive layer 2.
[0032] The melt flow rate (MFR) of the acid-modified polyolefin forming the electrode adhesive layer 2 is preferably 3 g / 10 min or more and 30 g / 10 min or less, and more preferably 5 g / 10 min or more and 10 g / 10 min or less.
[0033] When the MFR of the acid-modified polyolefin forming the electrode adhesive layer 2 is 3 g / 10 min or more, the acid-modified polyolefin sufficiently wraps around the electrode lead wire 11 during thermocompression bonding, making it easy to seal the periphery of the electrode lead wire 11.
[0034] When the MFR of the acid-modified polyolefin forming the electrode adhesive layer 2 is 30 g / 10 min or less, the electrode adhesive layer 2 is less likely to become excessively thin during thermocompression bonding, making it easier to ensure adhesive strength.
[0035] The thickness of the electrode adhesive layer 2 is preferably as thin as possible while still allowing thermocompression bonding with the electrode lead wire 11. For example, the thickness of the electrode adhesive layer 2 is preferably 20 μm or more and 30 μm or less. When the thickness of the electrode adhesive layer 2 is 20 μm or more, sufficient adhesive strength between the electrode adhesive layer 2 and the electrode lead wire 11 can be ensured. When the thickness of the electrode adhesive layer 2 is 30 μm or less, the heat resistance of the sealing film 1 can be easily ensured.
[0036] (Sealant layer) The sealant layer 3 is a layer that is fused to, for example, a battery container by heating and pressurizing. The container will be described later. The surface of the sealant layer 3 is the other surface 1b of the sealing film 1.
[0037] The sealant layer 3 mainly contains an acid-modified polyolefin. In this specification, the sealant layer 3 "mainly contains an acid-modified polyolefin" means that the content of the acid-modified polyolefin is the highest among the resins constituting the sealant layer 3. The sealant layer 3 preferably contains 50% by mass or more of the acid-modified polyolefin based on the total amount of the sealant layer 3. The sealant layer 3 preferably contains 80% by mass or more of the acid-modified polyolefin based on the total amount of the sealant layer 3.
[0038] In the sealant layer 3, optional components other than the acid-modified polyolefin include known additives such as stabilizers, antistatic agents, and colorants.
[0039] As the acid-modified polyolefin, acid-modified PP is preferable because of its excellent heat resistance. As the acid-modified PP, the acid-modified PP exemplified as the material of the electrode adhesive layer 2 described above is preferably used. Among them, as the acid-modified PP, a polymer obtained by acid-modifying a random copolymer of ethylene and propylene is preferable because of its excellent flexibility.
[0040] The acid-modified polyolefin constituting the sealant layer 3 preferably contains at least one of acid-modified PP and acid-modified polyethylene.
[0041] The sealant layer 3 preferably contains an acid-modified PP to increase the strength of the fusion site with the battery container. On the other hand, when the sealant layer 3 contains an acid-modified PP, the melting point of the sealant layer 3 increases as the content of the acid-modified PP increases. Therefore, if the content of the acid-modified PP in the sealant layer 3 is too high, the heating temperature (heat seal temperature) when the sealant layer 3 is fused becomes too high, and the electrode adhesive layer 2 may deteriorate.
[0042] Therefore, it is more preferable that the sealant layer 3 contains both the acid-modified PP and the acid-modified polyethylene, which can lower the melting point of the sealant layer 3 and the heating temperature when fusing the sealant layer 3, thereby suppressing deterioration of the electrode adhesive layer 2.
[0043] The acid group of the acid-modified polyethylene is preferably a maleic anhydride group, i.e., the acid-modified polyethylene is preferably maleic anhydride-modified polyethylene.
[0044] In the resin constituting the sealant layer 3, the proportion of the acid-modified PP with respect to the total of the acid-modified PP and the acid-modified polyethylene is preferably 20% by mass or more and 80% by mass or less.
[0045] The melting point of the resin forming the sealant layer 3 is preferably 100° C. or higher and 160° C. or lower. When the “resin forming the sealant layer 3” is a polymer alloy of two or more types of resin, the “melting point of the resin forming the sealant layer 3” means the melting point of the polymer alloy forming the sealant layer 3.
[0046] The MFR of the resin forming the sealant layer 3 is preferably 3 g / 10 min or more and 30 g / 10 min or less, and more preferably 5 g / 10 min or more and 10 g / 10 min or less. When the MFR of the resin forming the sealant layer 3 is within the above range, the sealing film 1 can be easily produced, which is preferable.
[0047] The thickness of the sealant layer 3 is preferably as thin as possible while still allowing thermocompression bonding to the storage container. For example, the thickness of the sealant layer 3 is preferably 20 μm or more and 40 μm or less. If the thickness of the sealant layer 3 is 20 μm or more, the fusion strength between the sealant layer 3 and the storage container may be reduced. If the thickness of the sealant layer 3 is greater than these ranges, the heat resistance of the sealing film 1 may be poor.
[0048] The sealant layer 3 preferably has the same thickness as the electrode adhesive layer 2 .
[0049] (Middle class) The intermediate layer 4 is provided between the electrode adhesive layer 2 and the sealant layer 3 .
[0050] The intermediate layer 4 mainly contains a fluororesin. In this specification, the intermediate layer 4 "mainly contains a fluororesin" means that the content of the fluororesin is the highest among the resins constituting the intermediate layer 4. The intermediate layer 4 preferably contains 50% by mass or more of the fluororesin based on the total amount of the intermediate layer 4. The intermediate layer 4 preferably contains 80% by mass or more of the fluororesin based on the total amount of the intermediate layer 4.
[0051] When the intermediate layer 4 contains a fluororesin, the sealing film 1 can easily suppress the penetration of moisture.
[0052] The fluororesin used for the intermediate layer 4 is preferably polychlorotrifluoroethylene (PCTFE), which is excellent in mechanical strength, gas barrier properties, moldability, and the like among fluororesins.
[0053] The thickness of the intermediate layer 4 is 30% or more and 75% or less of the total thickness of the sealing film 1. The thickness of the intermediate layer 4 is preferably 33% or more of the total thickness of the sealing film 1. In addition, the thickness of the intermediate layer 4 is preferably 73% or less of the total thickness of the sealing film 1.
[0054] The thickness of the intermediate layer 4 is preferably equal to or greater than the thickness of the electrode adhesive layer 2 .
[0055] The thickness of the intermediate layer 4 is preferably equal to or greater than the thickness of the sealant layer 3 .
[0056] Specifically, the thickness of the intermediate layer 4 is preferably not less than 30 μm and not more than 120 μm.
[0057] <Electrode lead wire components> 2, the electrode lead member 10 has an electrode lead 11 and the above-mentioned sealing film 1. The electrode lead member 10 shown in FIG.
[0058] The pair of sealing films 1 are in contact with each other with their electrode adhesive layers 2 facing each other. In Fig. 2, the surfaces 1a on the electrode adhesive layer 2 sides are in contact with each other.
[0059] The pair of sealing films 1 also cover the electrode lead wire 11 by being in contact with the entire circumference of the electrode lead wire 11 in the circumferential direction.
[0060] [Electrode lead wire] The electrode lead wire 11 has a lead wire body 111 and a surface treatment layer 112 .
[0061] (Lead wire body) Lead wire body 111 is conductive and allows current to flow between the inside and outside of the battery. Known metals such as aluminum, copper, nickel, iron, gold, platinum, and various alloys can be used as the material of lead wire body 111. Among these materials, aluminum and copper are preferred because they have excellent conductivity and are cost-effective.
[0062] The surface of the lead wire body 111 may be nickel-plated. The nickel plating of the lead wire body 111 may be electroplated using a Watts bath containing nickel sulfate, nickel chloride, boric acid, or the like as main components. The nickel plating of the lead wire body 111 is preferably performed using a nickel sulfamate plating bath containing nickel sulfamate and boric acid as main components. The plating film formed by this method has excellent flexibility and is less likely to crack.
[0063] The lead body 111 is preferably an aluminum plate or a nickel-plated copper plate.
[0064] (Surface treatment layer) A corrosion-resistant surface treatment layer 112 may be formed on the surface of lead body 111. In this specification, "corrosion resistance" refers to the property of being less susceptible to corrosion by the electrolyte inside a battery.
[0065] Examples of the surface treatment layer 112 include an acid-resistant coating made of a material such as a phosphate, a chromate, a fluoride, or a triazine thiol compound. These acid-resistant coatings can be formed by subjecting the lead wire body 111 to a chemical conversion treatment.
[0066] The surface treatment layer 112, which is an acid-resistant coating, prevents delamination between the lead wire body 111 and the sealing film 1. In addition, the surface treatment layer 112, which is an acid-resistant coating, suppresses dissolution or corrosion of the surface of the lead wire body 111 when the electrolyte used in the battery reacts with moisture to produce hydrogen fluoride. In particular, when the lead wire body 111 is made of aluminum, the surface treatment layer 112 suppresses dissolution and corrosion of aluminum oxide present on the surface of the lead wire body 111.
[0067] The surface treatment layer 112 is preferably a coating formed by a chromate phosphate treatment using three components: phenol resin, chromium trifluoride, and phosphoric acid.
[0068] Alternatively, the surface treatment layer 112 is preferably a coating formed by treatment with a chemical conversion treatment agent containing a resin component containing at least a phenol resin and a metal such as molybdenum, titanium, or zirconium, or a metal salt of molybdenum, titanium, or zirconium.
[0069] As a method of chemical conversion treatment, a known technique can be used. For example, by immersing a metal in the above-mentioned chemical conversion treatment agent, a reaction between the metal and the chemical conversion treatment agent occurs on the metal surface, and an insoluble product that adheres to the metal surface is generated. The generated insoluble product functions as the above-mentioned acid-resistant coating.
[0070] At the end 1c of the sealing film 1 of the electrode lead member 10 as described above, the intermediate layer 4 having a fluororesin that is difficult for moisture to permeate is exposed over 30% to 75% of the entire thickness of the sealing film 1. That is, in an area of 30% to 75% of the entire end 1c of the sealing film 1, the intrusion of moisture into the sealing film 1 is suppressed.
[0071] Furthermore, in an area of 67% or less of the end portion 1c of the sealing film 1 excluding the area corresponding to the intermediate layer 4, moisture may penetrate into the sealing film 1. Here, since the intermediate layer 4 is located between the electrode adhesive layer 2 and the sealant layer 3, the area through which moisture can penetrate into the sealing film 1 is divided into two and narrowed. Therefore, moisture is less likely to penetrate from the end portion 1c of the sealing film 1 in the direction of the arrow indicated by the symbol X.
[0072] Furthermore, the sealing film 1 contains an acid-modified polyolefin as a material for forming the electrode adhesive layer 2. Therefore, the electrode adhesive layer 2 is easily heat-sealed to the electrode lead wire 11, and the interface between the electrode lead wire 11 and the sealing film 1 is easily sealed.
[0073] The sealing film 1 contains acid-modified polyolefin as a material for forming the sealant layer 3. Therefore, the sealant layer 3 is easily heat-sealed with the resin material constituting the battery container, and easily seals the interface between the container and the sealing film 1.
[0074] As a result, the sealing film 1 of the present embodiment is a sealing film that easily provides sealing and easily prevents moisture from entering.
[0075] Furthermore, since the electrode lead member 10 of this embodiment includes the sealing film 1, it becomes an electrode lead member that is easy to seal and easily prevents moisture from entering.
[0076] <Battery> 3 is a schematic perspective view showing a battery 100 of this embodiment. The battery 100 has the electrode lead member 10 of this embodiment described above, a container 20, and a lithium ion battery 30.
[0077] The storage container 20 has a container body 21 and a lid 22 .
[0078] The container body 21 is obtained by drawing a laminate for battery exterior packaging. The container body 21 has a recess 21a for accommodating the lithium ion battery 30. The laminate for battery exterior packaging will be described later.
[0079] The lid 22 is made of a laminate for battery exterior packaging and has the same area as the container body 21 in a plan view.
[0080] The storage container 20 is formed by overlapping a container body 21 and a lid 22 and heat sealing the four edges 25.
[0081] The container body 21 and the lid 22 may be integrally formed. Specifically, a rectangular laminate for battery exterior packaging is prepared, and a recess is formed by drawing one end side of the center in the longitudinal direction, to form a member in which the container body 21 and the lid 22 are integrally formed. Such a member can be formed into the storage container 20 by folding the laminate for battery exterior packaging from the center in the longitudinal direction so as to close the recess, and heat sealing the edges on all four sides.
[0082] FIG. 4 is a cross-sectional view taken along line IV-IV in FIG. The battery exterior laminate, which is the material of the container body 21 and the lid 22, has a metal foil 201, a sealant layer 202 provided on one side of the metal foil 201, and a film substrate 203 provided on the other side of the metal foil 201.
[0083] That is, the container body 21 and the lid 22 each have a metal foil 201 , a sealant layer 202 , and a film substrate 203 .
[0084] The metal foil 201 may be an aluminum foil, a stainless steel foil, a copper foil, an iron foil, etc. The metal foil 201 may be subjected to a surface treatment such as a chemical conversion treatment.
[0085] The sealant layer 202 is in contact with the sealant layer 3 of the sealing film 1 and is heat-sealed thereto.
[0086] The resin forming the sealant layer 202 is selected from those that can be fused to the sealing film 1. Examples of the resin forming the sealant layer 202 include polypropylene-based resins, and polypropylene homopolymers, copolymers of polypropylene and ethylene, and the like can be used.
[0087] As the polyethylene-based resin, low-density polyethylene, linear low-density polyethylene, or the like can be used.
[0088] The resin constituting the film substrate 203 is not particularly limited, but polyamide, polyethylene terephthalate (PET), phenol resin, polypropylene, and the like, which have high strength, are preferably used.
[0089] 3 and 4, in the battery 100, the electrode lead member 10 is drawn from the inside (recess 21a) of the storage container 20 to the outside of the storage container 20. In addition, the electrode lead member 10 is fused to the sealant layer 202 of the storage container 20 at the sealing film 1.
[0090] According to the battery 100 configured as above, since the electrode lead member 10 has the above-mentioned sealing film 1, the intrusion of moisture from around the electrode lead 11 into the inside of the storage container 20 is suppressed. Therefore, the battery 100 is resistant to deterioration and has high reliability.
[0091] Although the preferred embodiment of the present invention has been described above with reference to the accompanying drawings, the present invention is not limited to the above embodiment. The shapes and combinations of the components shown in the above embodiment are merely examples, and various modifications can be made based on design requirements, etc., without departing from the spirit of the present invention. EXAMPLES
[0092] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0093] A sealing film was produced in which an electrode adhesive layer, an intermediate layer, and a sealant layer were laminated in this order using the resin described below. The resins that were the raw materials for each layer were separately heated and melted, and simultaneous multilayer film formation was performed using an extruder capable of simultaneous multilayer extrusion molding. Furthermore, the ends in the width direction of the obtained laminate were slit and cut off to produce the original rolls of the sealing films of each Example and Comparative Example. The width of the original roll of the sealing film was 250 mm.
[0094] Electrode adhesive layer: Maleic anhydride modified polypropylene (MFR 7.5g / 10min, melting point 135℃) Middle layer: PCTFE (polychlorotetrafluoroethylene) Sealant layer: 1:1 (mass ratio) blend of maleic anhydride polyethylene and maleic anhydride polypropylene
[0095] Maleic anhydride modified polypropylene is a polymer obtained by graft polymerizing maleic anhydride onto a random copolymer of ethylene and propylene.
[0096] In the following examples and comparative examples, the following resins were used. Maleic anhydride modified polypropylene: Admer QF060 (Mitsui Chemicals, Inc.) Maleic anhydride modified polyethylene: Admer NF518 (Mitsui Chemicals, Inc.) PCTFE: DF0050-C1 (manufactured by Daikin Industries, Ltd.)
[0097] The thickness of each layer of the produced sealing film is shown in Tables 1 and 2.
[0098] [Table 1]
[0099] [Table 2]
[0100] From each of the obtained original sheets of sealing film, sealing films were cut out as follows, and each evaluation was performed.
[0101] <Preparation of electrode lead wire member> Square aluminum foil and copper foil were used as electrode lead wires, each with dimensions of 50 mm width × 50 mm length × 300 μm thickness.
[0102] The copper foil is made of Ni(NH 2 SO 3 ) 2 4H 2 O: 500g / l, NiCl 2 6H 2 O: 30g / l, H 3 BO 3 The plating was carried out using a plating bath with a composition of 50 g / l of cadmium hydroxide and 5 ml / l of sodium lauryl sulfate. The plating conditions were a bath temperature of 50°C and a current density of 10 A / dm 2 It was decided.
[0103] A surface treatment layer made of glyceryl chitosan dissolved in water was applied to the surface of the two types of electrode lead wires and then dried to form a surface treatment layer made of glyceryl chitosan. The thickness of the surface treatment layer was 0.8 μm.
[0104] Two rectangular pieces of sealing film, each having a width of 15 mm and a length of 60 mm, were cut out from each original sealing film. When cutting out the sealing films, the width direction of the original sealing film was aligned with the width direction of the sealing film to be cut out.
[0105] As shown in FIG. 5, a set of sealing films 1A is placed over the electrode lead wires 11A, and is sealed at 190° C. and 2 kgf / cm 2 using a heat sealer. 2 The heat sealer used had a pair of two seal bars, one of which was covered with an elastic body.
[0106] After the thermocompression bonding, the front and back sides of the obtained laminate were switched and thermocompression bonding was performed again under the above conditions to prepare an electrode lead member 10A.
[0107] Sample A was an electrode lead wire member in which aluminum foil was used as the electrode lead wire 11A. Also, sample B was an electrode lead wire member using nickel-plated copper foil as the electrode lead wire 11A.
[0108] <Preparation of Laminate for Battery Exterior> A 12 μm thick biaxially oriented PET film, a 40 μm thick aluminum foil, and a 40 μm thick ethylene-propylene random copolymer film were dry laminated and cut into a square with each side measuring 100 mm to produce a laminate 200 for battery exterior packaging.
[0109] The aluminum foil corresponds to the above-mentioned metal foil 201. The random copolymer film corresponds to the above-mentioned sealant layer 202. The PET film corresponds to the above-mentioned film substrate 203.
[0110] <Fusion of electrode lead wire member and laminate for battery exterior> For each of Sample A and Sample B, the sealant layer of the sealing film 1A and the random copolymer film (sealant layer) of the laminate for battery exterior packaging 200 were overlapped and heat sealed.
[0111] Specifically, as shown in FIG. 6, an electrode lead 11A of an electrode lead member 10A and two laminates 200 for battery exterior packaging were placed and overlapped with their centers aligned and their sides parallel to each other.
[0112] The portion of the electrode lead member 10A where the sealing film 1A exists is sealed from both sides of the laminate 200 for battery exterior packaging using a heat sealer at 190° C. and 2 kgf / cm 2 The laminate was heat-sealed under conditions of 100° C., 10 seconds, and 5 seconds to obtain a laminate in which the laminate for battery exterior packaging 200 was fused to both sides of the electrode lead wire member 10A.
[0113] <Measuring the bonding strength> The obtained laminate was cut at the position indicated by the dashed line Y in Fig. 6 to prepare a test piece for measuring the bonding strength. Fig. 7 is a cross-sectional view of the test piece.
[0114] The 180-degree peel strength of the obtained test piece was measured using an Instron tensile tester. The measurement was performed by holding the end α of the laminate for battery exterior 200 farther from the electrode lead wire 11 and the end β of the electrode lead wire 11 farther from the sealing film 1 with the gripping parts of the tester, and pulling in the direction of the double-headed arrow A in FIG. 7 at a speed of 10 mm / min.
[0115] Moreover, the peel strength was measured for each of the two laminates 200 for battery exterior packaging.
[0116] The electrode lead wire members 10A in which both of the laminates 200 for battery exteriors had a peel strength of 100 N / 30 mm or more were evaluated as non-defective (◯), and the rest were evaluated as defective (×).
[0117] <Sealing test> For each of samples A and B, a penetrant liquid prepared by dissolving a red dye in a hydrocarbon solvent was dropped onto the edge of the thermocompression bonded portion between the electrode lead wire 11A and the sealing film 1A. The penetrant liquid was dropped onto both sides in the width direction of the sealing film 1A.
[0118] After dropping the penetrant liquid, the electrode lead wire member 10A was observed from both the front and back sides through the sealing film 1. Samples in which penetration of the penetrant liquid from the edge of the electrode lead wire 11 to the interface between the electrode lead wire 11A and the sealing film 1A was not observed were evaluated as good (◯), and samples in which penetration was observed were evaluated as bad (×).
[0119] <Hardness test> For each of the electrode lead members 10A of Examples 1 to 6 and Comparative Examples 1 to 4, the sealing film 1A protruding from the end of the electrode lead 11A was folded 180 degrees to one side along the end of the electrode lead 11 (first time), and then folded 180 degrees to the other side (second time), and the occurrence of whitening was observed. The area where whitening was observed was the area where the sealing film 1A was folded the second time. This was the surface of sealing film 1A, which was the front side.
[0120] The state of whitening occurring on the sealing film 1 was observed and evaluated as ◯, △, or × as follows. The sealing films with the state of whitening of ◯ or △ were evaluated as passing. (Evaluation Criteria) ◯: No whitening observed. △: Whitening was observed in the folded portion, but the electrode lead wire was visible through the folded portion. Furthermore, when the bent portion was observed under a magnified optical microscope (magnification 40x), no cracks were found. ×: The following (1) or (2) applies. (1) The bent portion turns white, and the electrode lead wire cannot be seen through the bent portion. (2) When the folded part is observed under a magnified optical microscope (magnification 40x), cracks can be seen in the folded part.
[0121] <Barrier property evaluation> The water vapor permeability of each film was measured according to JIS K 7129-2 "Plastics - Films and sheets - Determination of water vapor permeability - Part 2: Infrared sensor method". If the water vapor permeability value of the film is large, more water will penetrate into the battery through the film. Conversely, if the water vapor permeability value is small, less water will penetrate into the battery.
[0122] In this embodiment, the intrusion of moisture from the external environment through the end face of the sealing film was evaluated by the above-mentioned evaluation method. The barrier performance of the end face is the key to the moisture blocking performance from the end face, not the surface direction of the sealing film. The end face of the intermediate layer made of fluororesin can suppress the intrusion of moisture from the end face of the sealing film, so the degree of moisture intrusion from the end face of the sealing film is affected by the barrier properties of the electrode adhesive layer and the sealant layer.
[0123] When the electrode adhesive layer and the sealant layer are heat-sealed to their respective adherends, they are heated and melted to solidify. At this time, the thickness of each of the electrode adhesive layer and the sealant layer is reduced, and the proportion of the electrode adhesive layer and the sealant layer in the total thickness of the sealing film is reduced. Therefore, it is considered that the thickness of the intermediate layer becomes dominant with respect to the intrusion of moisture from the end surface of the sealing film.
[0124] In this embodiment, the above evaluation method was adopted because it was thought that by measuring the water vapor barrier performance in the surface direction of the entire sealing film, it would be possible to discuss the penetration of moisture from the end face direction in a pseudo manner.
[0125] The evaluation results are shown in Tables 3 and 4 below.
[0126] [Table 3]
[0127] [Table 4]
[0128] From Tables 1 and 2, it was confirmed that the basic bonding strength and sealing performance of the laminate film to which the electrodes were bonded were sufficient in Examples 1 to 6 and Comparative Examples 1 and 3. In Comparative Examples 2 and 4, the electrode adhesive layer and sealant layer were thin, so the bonding strength was insufficient.
[0129] The results of the hardness test were judged based on the degree of whitening, but there were no samples with a large amount of whitening.
[0130] In addition, the measurement results of the water vapor transmission rate showed that the sealing films of Examples 1 to 6 had a water vapor transmission rate of 0.16 g / m 2 This indicates that the vapor barrier performance is sufficient.
[0131] On the other hand, the sealing films of Comparative Examples 1 and 3 had a water vapor permeability of 0.3 g / m 2·days, indicating that the water vapor barrier performance is poor. In other words, it is suggested that the sealing films of Comparative Examples 1 and 3 may allow a large amount of moisture to penetrate into the battery. Therefore, it can be determined that the sealing films of Comparative Examples 1 and 3 are unsuitable as battery components, even though they have good bonding strength and sealing performance.
[0132] From the above results, it was found that the present invention is useful. [Explanation of symbols]
[0133] 1, 1A... sealing film, 1a, 1b... surface, 2... electrode adhesive layer, 3, 202... sealant layer, 4... intermediate layer, 10, 10A... electrode lead wire member, 11, 11A... electrode lead wire, 100... battery, 111... lead wire body, 112... surface treatment layer
Claims
1. An electrode adhesive layer; A sealant layer; A sealing film having an intermediate layer provided between the electrode adhesive layer and the sealant layer, the electrode adhesive layer and the sealant layer contain maleic anhydride modified polyolefin, The intermediate layer contains a fluororesin, The thickness of the intermediate layer is 30% or more and 75% or less of the total thickness of the sealing film, The sealant layer comprises a sealing film containing both maleic anhydride modified polyethylene and maleic anhydride modified polypropylene in a mixed state.
2. The sealing film according to claim 1 , wherein the intermediate layer has a thickness equal to or greater than a thickness of the electrode adhesive layer.
3. The sealing film according to claim 1 or 2, wherein the thickness of the intermediate layer is equal to or greater than the thickness of the sealant layer.
4. The sealing film according to claim 1 , wherein the fluororesin is polychlorotrifluoroethylene.
5. The sealing film according to claim 1 , wherein the electrode adhesive layer and the sealant layer are made of different materials.
6. An electrode lead wire extending in one direction; An electrode lead member comprising the sealing film according to claim 1 .
7. a pair of the sealing films sandwiching the electrode lead wire; The electrode lead member according to claim 6 , wherein the pair of sealing films are in contact with each other such that the electrode adhesive layers face each other and are in contact with the entire circumferential circumference of the electrode lead wire to cover the electrode lead wire.
8. The electrode lead wire includes a lead wire body and a surface treatment layer formed on the surface of the lead wire body, The electrode lead member according to claim 6 or 7, wherein the sealing film is provided in the electrode adhesive layer so as to be in contact with the surface treatment layer.
9. A battery comprising the electrode lead member according to any one of claims 6 to 8.
Citation Information
Patent Citations
Film for lead wire of battery and packaging material for battery using the same
JP2003007268A
Adhesive film for metal terminal
JP2017139120A